Painless Project Management with FogBugz - Gunderloy, Michael (Apress : Imprint: Apress, 2005)
Many programs purport to help a development team manage a project but most of them aren't very good. Enter FogBugz. This dynamic tool is based on keeping track of a database of cases. At any given time, cases are assigned to one person, who must resolve or forward them to someone else. With FogBugz, cases can be prioritized, documented, sorted, discussed, edited, assigned, estimated, searched, and tracked. And because FogBugz is web-based, everyone on a development team has access to the whole picture, at any given moment. That picture may include everything from customer feature requests, to high-level design discussions, to tiny bug fix details. This book (written under the guidance of the entire FogBugz team) completely describes the ins and outs of the latest version of FogBugz.